THE ROLE OF LEGAL CULTURE IN THE SPIRITUAL AND MORAL EDUCATION OF YOUTH (American Journal of Research in Humanities and Social Sciences, 2024)
This article analyzes the impact of modern information and communication technologies on youth spirituality and moral education, changes in their way of life and negative effects of globalization. Young people face social and spiritual threats, and their way of thinking and behavior is influenced by information attacks. It is important in the formation of a legal culture in young people and strengthening spiritual education, ensuring the stability of society. The article will highlight the role of the state and the public in the formation of the attitude of young people towards spiritual and moral values, as well as propose measures that should be carried out to develop their legal and spiritual thinking.